Effects of climate change on deepwater oxygen and winter mixing in a deep lake (Lake Geneva): Comparing observational findings and modeling. Issue 11 (18th November 2016) - Schwefel, Robert; Gaudard, Adrien; Wüest, Alfred; Bouffard, Damien
Abstract: Low concentrations of dissolved oxygen remain a global concern regarding the ecological health of lakes and reservoirs. In addition to high nutrient loads, climate‐induced changes in lake stratification and mixing represent additional anthropogenic menace resulting in decreased deepwater oxygen levels. The analysis of 43 years of monitoring data from Lake Geneva shows no decreasing trend neither in the areal hypolimnetic mineralization rate nor in the extent of hypoxia. Instead, hypoxic conditions are predominantly controlled by deep mixing in winter and much less by the trophic variations over the past decades. To reproduce winter mixing, the one‐dimensional hydrodynamic model SIMSTRAT was specially adapted to deep lakes and run for several climate scenarios. The simulations predicted a decrease in the maximum winter mixing depth from an average of ∼172 m for 1981–2012 to ∼136 m and ∼127 m in response to predicted atmospheric temperatures between 2045–2076 and 2070–2101 according to Intergovernmental Panel on Climate Change scenarios. Concurrently, events with complete homogenization of temperature and oxygen in winter will decrease by ∼50%. Consequently, the hypolimnetic oxygen concentrations will significantly decrease. These results demonstrate that changes in deep mixing can have stronger impact than eutrophication on the deepwater oxygen levels of oligomictic lakes. Key Points: A one‐dimensional model reproduces temperature, convective winter mixing, and oxygen in a deep lake Decadal deepwater oxygen variations are to a large extent controlled by convective mixing in winter Hypolimnetic oxygen will likely decrease in Lake Geneva by the end of the century, though not to the level of permanent hypoxia